Social Cognitive Theory and Role of Key Actors in YouTube Comment Networks on Turmeric for Health - Hana, Risma Zahra; Rita Destiwati (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research examines the dissemination of health information on YouTube, specifically focusing on discussions in video comment sections about the use of turmeric as an alternative medicine, a topic deeply rooted in traditional Indonesian medicine. This study aims to identify key actors and understand the process of information dissemination formed in the comments of the YouTube video “Manfaat dan Cara Membuat Kunyit yang Benar untuk Kesehatan”. Using Bandura's Social Cognitive Theory with social network analysis method combined with content analysis. Network analysis identified @dr.emasuperr as a source of scientific information and @saptayusmana7022 as an empirical validator, which together form a decentralized network structure. Findings revealed a dynamic mechanism of reciprocal determinism: (1) personal (individual beliefs formed through user testimonials), (2) behavioral (adoption of health practices), and (3) environmental (social support and medical authority) influence each other. The interaction of these three SCT components creates a snowball effect in information dissemination.